The Impact of Organizational Climate and Professional Competence on Teachers' Performance - Sari, Nani Yulia; Kristiawan, Muhammad; Suherman, Suherman (Journal of Social Work and Science Education, 2025)
This study determines the effect of organizational climate and professional competence on teacher’s performance partially and simultaneously at SMA Negeri 9 Palembang. Data collection techniques were carried out through questionnaires, observations, and documentation studies. The validity test used construction validity, while the reliability test used Cronbach’s alpha, linearity test, and normality test. The results state there is significant partial and simultaneous effect of organizational climate and professional competence on teacher’s performance at SMA Negeri 9 Palembang. The findings can help school administrators at SMA Negeri 9 Palembang design better policies to enhance organizational climate and teacher competence. Despite extensive research on teacher performance, few studies have examined the combined effect of organizational climate and professional competence in Indonesian high schools. Since both factors significantly influence performance, school leaders and policymakers can prioritize interventions such as workshops, mentorship, and a supportive work environment to boost teacher effectiveness. This study adds new insights by examining the dual influence of organizational climate and professional competence on teacher performance in a specific Indonesian school. Its practical value lies in guiding school leaders to enhance both workplace culture and teacher skills, while its academic contribution strengthens the literature with robust, context-specific evidence.